Daily administration of yokukansan and keishito prevents social isolation-induced behavioral abnormalities and down-regulation of phosphorylation of neuroplasticity-related signaling molecules in mice - Hironori Fujiwara; Yaoyu Han; Ken Ebihara; Suresh Awale; Ryota Araki; Takeshi Yabe; Kinzo Matsumoto (BMC, 2017)
Abstract Background Our previous studies demonstrated that post-weaning social isolation (ISO) in mice induces behavior abnormalities such as deficits of sociability- and attention-like behaviors. These deficits can be attenuated by methylphenidate (MPH), a drug used for attention deficit hyperactivity disorder (ADHD), suggesting that ISO mice offer a potential animal model of comorbid developmental disorder with ADHD and autism spectrum disorder symptoms. This study investigated the effects of Kampo formulae, yokukansan (YKS) and keishito (KST), on the neuropsychiatric symptoms of ISO mice to clarify the therapeutic or preventive/delaying potential of these formulae for the treatment of neurodevelopmental disorders. Methods Three-to-4-week old male ICR mice were socially isolated during an experimental period and YKS and KST (1523.6 and 2031.8 mg/kg, p.o.) was administered starting from week 2 and week 0 after starting ISO for the analysis of their therapeutic and preventive/delaying potentials, respectively. Sociability, attention-related behavior and fear memory were elucidated by a 3 chamber test, a water-finding test and fear conditioning test, respectively. Moreover, the phosphorylation of neuroplasticity-related signaling molecules in mice hippocampus was analyzed using western blotting. Results In a therapeutic procedure, YKS ameliorated ISO-induced impairments of attention-like behavior and context-dependent fear memory, but not of sociability, whereas KST had no beneficial effects in ISO mice. In experiments to analyze the preventive/delaying potentials of these treatments, both YKS and KST improved sociability, attention, and context-dependent fear memory deficits. The improvement of sociability in mice by YKS and KST was not inhibited by a dopamine D1 receptor antagonist, suggesting that YKS and KST improved the ISO-induced sociability deficit by other mechanisms besides activation of the dopaminergic system. On the other hand, the beneficial effects of YKS and KST on attention-like behavior were inhibited by a muscarinic antagonist, suggesting that YKS and KST ameliorated ISO-induced attention-like behavior through a cholinergic mechanism. Moreover, the phosphorylated forms of CaMKII and CREB were down-regulated by ISO stress and restored by YKS and KST administration. Conclusions These findings suggest that YKS and KST may be useful for the improvement of neurodevelopmental disorders.